1994
DOI: 10.1161/01.hyp.24.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II type 1 receptor gene polymorphisms in human essential hypertension.

Abstract: We conducted the present study to determine whether the angiotensin II type I receptor (AT,) gene might be implicated in human essential hypertension by using case-control and linkage studies. The entire coding and 3' untranslated regions of the AT, receptor gene (2.2 kb) were amplified by polymerase chain reaction and submitted to single-strand conformation polymorphism in 60 hypertensive subjects with a familial susceptibility. We identified five polymorphisms (T 573 -»C, A 1062 -*G, A" 6 6^C , G 1 5 "^T, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
441
11
10

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 657 publications
(476 citation statements)
references
References 31 publications
14
441
11
10
Order By: Relevance
“…In the AT1 receptor gene five polymorphisms have been identified. However only A/C transversion at nucleotide position 1166 in the 3' un-translated region of the AT1R gene was found to be associated with human essential hypertension as reported by Bonnardeaux et al (27). A significant increase in the allele frequency of C 1166 in hypertensive subjects was seen (0.36 versus 0.28 in normotensive subjects; x 2 = 6.8, p<0.01).…”
Section: Angiotensin II Type I Receptor (Atir)supporting
confidence: 60%
See 2 more Smart Citations
“…In the AT1 receptor gene five polymorphisms have been identified. However only A/C transversion at nucleotide position 1166 in the 3' un-translated region of the AT1R gene was found to be associated with human essential hypertension as reported by Bonnardeaux et al (27). A significant increase in the allele frequency of C 1166 in hypertensive subjects was seen (0.36 versus 0.28 in normotensive subjects; x 2 = 6.8, p<0.01).…”
Section: Angiotensin II Type I Receptor (Atir)supporting
confidence: 60%
“…Despite this, it is postulated that the AT1 receptor polymorphism may be associated with functional alterations in the responsiveness of this receptor. Some authors (28-30) confirmed these results of Bonnardeaux et al (27) but others did not (31-33). Benetos et al (33) did not show association of this polymorphism with essential hypertension; but reported an association with aortic stiffness and with ratio of total to high-density lipoprotein cholesterol.…”
Section: Angiotensin II Type I Receptor (Atir)mentioning
confidence: 84%
See 1 more Smart Citation
“…The ACE I/D polymorphism and the angiotensin II type 1 receptor 1166 A/C and type 2 receptor 3123C/A polymorphisms are suspected to be markers in linkage disequilibrium with an unidentified functional variant that could affect the regulation of the gene in response to angiotensin II. 34 Moreover, the cellular effects of angiotensin II are mediated by two structurally distinct receptor subtypes, angiotensin II type 1 and type 2 receptors, and angiotensin II type 1 and type 2 receptors have opposite functions. [35][36][37] It is also suspected that angiotensin II receptor stimulates the kininogenkinin system and induces cough; therefore it was interesting for us to examine the association between angiotensin II receptor polymorphisms and ACE-inhibitor-related cough.…”
Section: Discussionmentioning
confidence: 99%
“…These efforts resulted in the identification of an A1166C variant that is confined to the 3′ untranslated region of the AT1R cDNA (Bonnardeaux et al 1994;Wang et al 1997) and has been implicated in determining mRNA stability and, ultimately, receptor expression (Thekkumkara and Linas 2003; Fig. 13).…”
Section: Genetic Variants In the Angiotensin II Receptor Type Imentioning
confidence: 99%